Case Report: Praziquantel-induced flare-up reaction in a rare case of diclofenac-induced probable DRESS comorbid with acute clonorchiasis: diagnostic and therapeutic challenges - Li, Wei; Huang, Kaizhou; Chen, Ying; Huang, Yuping; Zheng, Yi; Zhong, Minhua; Jiang, Kaiping; Ma, Xiaojun (Frontiers in Medicine, 2025)
Drug reaction with eosinophilia and systemic symptoms (DRESS), a severe T-cell-mediated hypersensitivity with mortality up to 10%, may progress to life-threatening multi-organ failure and culminate in multiple drug hypersensitivity (MDH). Clonorchiasis, a hepatobiliary parasitic endemic in China, manifests with nonspecific symptoms including fever, jaundice, and abdominal discomfort. We report an unique case of diclofenac-induced probable DRESS comorbid with acute clonorchiasis in which a praziquantel (PZQ)-related flare-up reaction occurred in a 42-year-old male. Following praziquantel administration, the patient exacerbated skin lesions, acute liver/kidney failure, likely triggered by Clonorchis sinensis lysis-released antigens amplifying IgE-mediated responses and PZQ-induced hepatic injury. Despite the reaction onset exceeding PZQ's peak concentration timeline, a type IV hypersensitivity reaction to PZQ cannot be ruled out. Therapeutic intervention with plasmapheresis, continuous renal replacement therapy, intravenous immunoglobulin, and systemic corticosteroids achieved clinical stabilization. One year later, the patient developed isolated hepatitis following administration of a structurally unrelated nonsteroidal anti-inflammatory drug. Combined with previous medical history, MDH was highly suspected. This case underscores the diagnostic complexity in distinguishing parasitic infections from DRESS through parasitological confirmation, herpesvirus reactivation profiling, validated DRESS criteria, and lesional skin histopathology. Therapeutically, stepwise immunomodulatory prioritization for DRESS control is essential, with PZQ therapy restricted to life-threatening parasitosis only after achieving immune stability, under intensive monitoring for hypersensitivity recrudescence and end-organ damage.